Prospek Penerapan Teknologi Nano dalam Pertanian dan Pengolahan Pangan di Indonesia - Ening Ariningsih (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
EnglishThe fast growing research in the field of nanotechnology in the last decade is a challenge as well as an opportunity for Indonesia to participate in the world market. This paper aimed to assess the prospects of nanotechnology application in Indonesia, especially in agriculture and food processing. The study was conducted through a literature review. Nanotechnology has a promising prospect to be applied in Indonesia. However, the research, development, and application of nanotechnology in Indonesia grow slowly and are more focused on areas other than agriculture and food processing, such as electronics, energy, medicine, pharmacy, etc. Barriers to the development of nanotechnology in Indonesia among others are (1) inadequate nanotechnology facilities and dispersed sporadically in a number of institutions, (2) lack of synergism among research institutions working on nanotechnology, (3) less supporting human resources, and (4) limited budget. A number of studies reveal that nanotechnology application in agriculture and food processing in Indonesia includes fertilizers, antioxidants, preservatives, fortification, functional foods, nutraceuticals, smart packaging, etc. In order to support nanotechnology application in national agro-industry, some policies to implement are (a) developing nanotechnology research network at national level, (b) socialization of nanotechnology and its potential utilization in agriculture, (c) strengthening human resource capacity in nanotechnology, (d) developing nanotechnology research synergy, (e) developing the governance of nanotechnology research at IAARD, (f) setting research priorities of nanotechnology, and (g) developing collaboration with private parties.IndonesianPenelitian di bidang teknologi nano yang berkembang pesat dalam dekade terakhir merupakan tantangan dan peluang bagi Indonesia untuk ikut berperan dalam pasar dunia. Tulisan ini bertujuan untuk mengkaji prospek penerapan teknologi nano, khususnya pada bidang pertanian dan pengolahan pangan. Kajian dilakukan melalui studi pustaka yang relevan dengan penelitian, pengembangan, dan penerapan teknologi nano, khususnya pada bidang pertanian dan pengolahan pangan di Indonesia. Hasil pengkajian menunjukkan teknologi nano mempunyai prospek yang cerah untuk diterapkan di Indonesia, namun penelitian, pengembangan, dan penerapannya di Indonesia berkembang lambat dan lebih terfokus pada bidang selain pertanian dan pengolahan pangan, seperti elektronik, energi, kedokteran, dan farmasi. Hambatan perkembangan teknologi nano di Indonesia antara lain (1) fasilitas (sarana dan prasarana) teknologi nano yang kurang memadai dan tersebar di sejumlah institusi; (2) kurangnya sinergisme antarlembaga riset teknologi nano; (3) sumber daya manusia (SDM) yang kurang mendukung; dan (4) anggaran yang kurang memadai. Sejumlah studi mengungkapkan penerapan teknologi nano pada bidang pertanian dan pengolahan pangan di Indonesia, seperti pupuk, antioksidan, pengawet makanan, fortifikasi, pangan fungsional, nutrasetikal, dan kemasan pintar. Dalam rangka mendorong penerapan teknologi nano pada agroindustri nasional maka peningkatan penguasaan teknologi nano di bidang pertanian perlu terus diupayakan dan dapat ditempuh melalui (a) membangun jaringan riset teknologi nano pada lingkup nasional, (b) sosialisasi teknologi nano dan potensi pemanfaatannya di bidang pertanian, (c) memperkuat SDM teknologi nano, (d) mengembangkan sinergi penelitian teknologi nano, (e) mengembangkan tata kelola penelitian teknologi nano pada lingkup Badan Litbang Pertanian, (f) menetapkan prioritas penelitian teknologi nano, dan (g) mengembangkan kerja sama dengan pihak swasta.